2020
DOI: 10.1038/s41598-020-77030-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi favor invasive Echinops sphaerocephalus when grown in competition with native Inula conyzae

Abstract: In a globalized world, plant invasions are common challenges for native ecosystems. Although a considerable number of invasive plants form arbuscular mycorrhizae, interactions between arbuscular mycorrhizal (AM) fungi and invasive and native plants are not well understood. In this study, we conducted a greenhouse experiment examining how AM fungi affect interactions of co-occurring plant species in the family Asteracea, invasive Echinops sphaerocephalus and native forb of central Europe Inula conyzae. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…This agrees with our hypothesis that perennial plants will be more supported by mycorrhiza, and therefore have greater success in competition with the facultatively mycotrophic weedy annual plants and partially agrees with a review by Lin et al 24 . However, our findings are not similar to Callaway et al 19 or Řezáčová et al 29 , as these reported AM fungi supported weedy annuals (Centaurea melitensis or E. sphaerocephalus, respectively), when grown in competition with a perennial plant. Our current study agrees with Callaway et al 30 , in that the influence of AM symbiosis on competitive abilities of weedy or invasive plants are context-dependent and should not be generalized, highlighting the importance of assessing influences of AM fungi on specific plant species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This agrees with our hypothesis that perennial plants will be more supported by mycorrhiza, and therefore have greater success in competition with the facultatively mycotrophic weedy annual plants and partially agrees with a review by Lin et al 24 . However, our findings are not similar to Callaway et al 19 or Řezáčová et al 29 , as these reported AM fungi supported weedy annuals (Centaurea melitensis or E. sphaerocephalus, respectively), when grown in competition with a perennial plant. Our current study agrees with Callaway et al 30 , in that the influence of AM symbiosis on competitive abilities of weedy or invasive plants are context-dependent and should not be generalized, highlighting the importance of assessing influences of AM fungi on specific plant species.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our hypothesis, based on the ruderal nature of weedy annual plants, the single soil disturbance did not play a role in the performance of weedy annual plant E. annuus when grown in competition with perennial plant C. biennis, or C. canadensis when grown in competition with perennial S. jacobaea. In a previous study, a single soil disturbance did not influence performance of Inula conyzae, a native plant species when grown in competition with Echinops sphaerocephalus, a non-native invasive plant species common in Eastern Europe 29 , and the authors propose the lack of response to disturbance was likely due to a rapid recovery of CMNs following disturbance. We propose a similar rapid recovery of the CMNs occurred in our current study, and therefore, plants with intact CMNs were not at an advantage over plants with initially disturbed mycelium.…”
Section: S Jacoabea C Biennis F Mosseae R Irregularis F Mosseae R Irr...mentioning
confidence: 88%
See 1 more Smart Citation
“…In our study, AMF inoculants were prepared from fresh soils taken from the same sites as the processed soils used to grow cotton. It was our intention to work only with native populations, as exotic species have occasionally been shown to be less beneficial to plant growth and less interfunctional with other native macro‐ and microflora (Klironomos, 2003; Koziol & Bever, 2017; Kouadio et al., 2017; Rezacova et al., 2020). Therefore, soil specific effects are to be expected, by design.…”
Section: Resultsmentioning
confidence: 99%
“…An important feature of Asteraceae, which often manifests itself alongside allelopathic effects, is the ability to form arbuscular mycorrhiza (AM) and common mycorrhizal networks (CMN) (Bongard et al, 2013;Yuan et al, 2014;Li et al, 2016;Chagnon et al, 2019;Qin, Yu, 2019). For invasive species like Solidago canadensis (Astereae), Helianthus tuberosus (Heliantheae), and Echinops sphaerocephalus (Cardueae), it was shown that AM and CMN contribute to their distribution and introduction successes (Bongard et al, 2013;Dong et al, 2015, Awaydul et al, 2018, Řezáčová et al, 2020, Nacoon et al, 2021. Analysis of scientific literature has established four tribes (Anthemideae, Astereae, Cardueae and Senecioneae) that rely on AM in their distribution (Table 1, Fig.…”
mentioning
confidence: 99%